2004
DOI: 10.1007/s10147-004-0464-7
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal ultrasound-guided 12-core systematic biopsy of the prostate for patients with a prostate-specific antigen level of 2.5–20 ng/ml in Japan

Abstract: We demonstrated a high prostate cancer detection rate by the transperineal ultrasound-guided 12-core systematic biopsy method in patients with PSA levels of 2.5 to 20 ng/ml. Accordingly, if the number of core biopsies is further increased overall, except in patients with a large prostate volume, and if the indication for biopsy is decided based on the PSAD and %f PSA, then the cancer detection rate by the present method may be further improved, with fewer unnecessary biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Some studies have shown that prostate volume is a relevant variable for the detection of PC [32,33,34]. Uzzo et al [35] have reported a PC detection rate of 23% in prostates ≥50 ml and 38% in prostates <50 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that prostate volume is a relevant variable for the detection of PC [32,33,34]. Uzzo et al [35] have reported a PC detection rate of 23% in prostates ≥50 ml and 38% in prostates <50 ml.…”
Section: Discussionmentioning
confidence: 99%
“…3 When compared to TR biopsy, studies on extended transperineal (TP) biopsy have been relatively limited and there has been no consensus on standard extended TP biopsy protocol. [4][5][6][7][8][9][10][11][12][13] The lack of standardization at the moment is related to both TP and TR approaches.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 In the study by Yamamoto and colleagues, a 12-core transperineal prostate biopsy was taken from 300 patients with PSA 2.5 to 20 ng/mL and the cancer detection rate increased. 12 In another study, 10, 12, and 13 core prostate biopsies increased the cancer detection rate by 25%, 22%, and 35%, respectively. 1,13 In the study by Guichard and colleagues, the cancer detection rates of 6, 12, 18, and 21 core prostate biopsies were 31.7%, 38.7%, 41.5%, and 42.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…How many biopsies should be taken to maximize cancer detection? In this study, we compared the cancer detection rates of 8,10,12,16, and 20 core prostate biopsies in patients with suspected prostate cancer and prostatespecific antigen (PSA) ≤20 ng/mL.…”
Section: Introductionmentioning
confidence: 99%